Teachers Learning in Technology-Ethnoscience Professional Development and Its Impact on TPACK - Yohanes Freadyanus Kasi; Ari Widodo; Achmad Samsudin; Riandi Riandi (Jurnal Penelitian Pendidikan IPA, 2022)
This study investigates teachers' learning in technology-ethnoscience professional development for 3 months and its impact on science teachers' TPACK in East Nusa Tenggara (NTT)-Indonesia. These secondary school science teachers participate in PD that focuses on communication of information technology and ethnoscience-based materials and their applications in designing and conducting classroom instruction. Five science teacher instruments (n=28) were used, i.e. TPACK test questions, lesson plan analysis rubric, teaching observation sheets, response questionnaires and interview guides. Data is collected before, during, and after program implementation which is carried out every week. Descriptive statistics and Paired Sample T-Test were used for analysis. It was found that teachers' TPACK increased after studying in the program with significant benefits. In addition, the ability to design and implement learning changes to be more oriented towards technology-ethnoscience integration, but the benefits are not significant for all science teachers. This study suggests that teachers' PD programs in the future need to consider aspects of integrating technology in learning and the process is carried out not only when the program is run, but continues every day in class so as to create habits for science teachers. Indonesia currently needs more longitudinal PD to ensure that TPACK is integrated in science teaching and its usefulness for student learning outcomes